Removal of oil from oil palm empty fruit bunches spikelet using steam and water processes - Gomez, Javier Hernando Chavarro (2014)
The development of new low cost technologies to increase the oil recovery in the palm oil mill especially from the palm oil wastes has been an important goal for the industry to increase oil extraction performance. In addition to the crude palm oil (CPO) production, high amount of wastes are annually generated at the mill with remainedCPO attached to them. The empty fruit bunches (EFB) is the largest solid wastes produced and high amount of oil it is impregnated due to mechanical processes during CPO extraction. However, the EFB is thrown in the field without further processing. Initially, the EFB was analyzedto determine initial oil content.Then, the detection and identification of oil were performed using Sudan Red to achieve an insightful view of oil that located inside and on the surface of EFBspikelet. The study shows that the oil mainly located on the surface of spikelet, about 73.73  0.05 % from total residual oil. Furthermore, the comparison of oil recovery efficiency among processes using saturated steam, hot water, combined steam-water, combined water-steam and high pressure spray water and steam was carried out. As a result of this work, two methods showed the best oil extraction yield, indicating that over 88% and 92% of oil could be removed from theEFB spikelet by hydro solvent assisted extraction (HYSASE) and high pressure fluid spray system (HPFSS), respectively. Finally, the quality of oil that obtained by HYSASE and HPFSS was compared with the quality of oil that obtained from shredded and pressed EFB, indicating almost similar oil quality, except for PV, with the advantage that more oil could be recovered.The recovered residual oil probably is not suitable as edible oil on its own or to be blended with CPO obtained from the main process at the palm oil mill. However, it has potential to be used as a feedstock for biodiesel, bio-lubricant production and other applications. Thus, these methods provide non-chemical, environmental friendly and novel processes of residual CPO recovery from EFB.